Tomografia aplicada á migraçãoem tempo - SOARES, Patrícia da Trindade (2019)
The flatness of reflection events in common image gathers (CIG), when the migration velocity model is correct, is the basis of methods for migration velocity analysis. The differential semblance of CIG gathers is minimum when all events are flat. Using the differential semblance as objective function, the velocity estimation reduces to an optimization problem. The simulated annealing algorithm estimates time migration velocity model that better flattens the events in CIG. This strategy do not have the shortcomings of the conventional NMO/DMO loop for time velocity analysis. The algorithm was successfully applied to estimate the velocity model for pre-stack migration of the Marmousoft synthetic data set.